2022
DOI: 10.1021/acs.orglett.2c01997
|View full text |Cite
|
Sign up to set email alerts
|

Enantioselective Total Synthesis of (−)-Hamigeran F and Its Rearrangement Product

Abstract: Herein, we report the first enantioselective total synthesis of the highly complex hamigeran diterpenoid (−)-hamigeran F and its rearrangement product. The synthetic strategy features key steps of asymmetric hydrogenation, Horner−Wadsworth−Emmons olefination, and intramolecular Friedel−Crafts acylation to construct the [6,6,5]-tricyclic skeleton bearing three consecutive stereocenters, a sequence of steps involving Rosenmund reduction, Wittig reaction, dihydroxylation to assemble the α-acetoxy ketone group, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…449 Use of computer-assisted retro-synthetic analysis of the pupukeanane class of sesquiterpenoid MNPs identied several routes with unusual disconnections beyond those already precedented for manufacture of the compounds. 450 Diterpenoids ansellone G and hamigeran F, 451,452 eight phorbaketal congeners, 453 aromatic sterol myrmenaphthol A, and seco-sterols glaciasterol B and 6ketoaplidiasterol B have been synthesised for the rst time. 454,455 Complex tropolone-containing triterpenoid gukulenin B has also been prepared.…”
Section: Reviewmentioning
confidence: 99%
“…449 Use of computer-assisted retro-synthetic analysis of the pupukeanane class of sesquiterpenoid MNPs identied several routes with unusual disconnections beyond those already precedented for manufacture of the compounds. 450 Diterpenoids ansellone G and hamigeran F, 451,452 eight phorbaketal congeners, 453 aromatic sterol myrmenaphthol A, and seco-sterols glaciasterol B and 6ketoaplidiasterol B have been synthesised for the rst time. 454,455 Complex tropolone-containing triterpenoid gukulenin B has also been prepared.…”
Section: Reviewmentioning
confidence: 99%
“…The iridium-catalyzed asymmetric hydrogenation of racemic γ,δ-unsaturated β-keto esters bearing an exocyclic double bond via DKR was developed by Xie [75] et al With the chiral spiro iridium catalyst, Ir-SpiroPAP L3, a series of exocyclic γ,δ-unsaturated βketo esters containing a five-, six-, or seven-membered ring 46 were hydrogenated to the corresponding chiral allylic alcohols 47 in high yields with good to excellent enantioselectivities (87 to > 99% ee) and cis-selectivities (93:7 to > 99:1) (Scheme 39). In addition, the asymmetric hydrogenation of racemic α-aryl-β-ethoxycarbonyl cyclopentanones via DKR for the synthesis of chiral cyclopentanols with three contiguous stereocenters was also demonstrated by Xie [76] et al This reaction was successfully used for the synthesis of natural products such as (+)-burmaniol A, (À )hamigeran B [77] and (À )-hamigeran F. [78] Interestingly, when the α,β-unsaturated β'-keto esters 48 [79] were used as substrates in the iridium-SpiroPAP L3a catalyzed asymmetric hydrogenation (Scheme 40), the C=O and C=C bonds were hydrogenated sequentially in a single step, giving the corresponding chiral cyclic alcohols 49 bearing three contiguous stereocenters with excellent enantioselec- tivities (92 to > 99% ee) and diastereoselectivities (dr 95/5 to > 99/1). The main reason for this unexpected result was that the electron-withdrawing α-ester group polarized the C=C bond, making it more susceptible to hydrogenation.…”
Section: Asymmetric Hydrogenation Of Keto Estersmentioning
confidence: 99%
“…In addition, the asymmetric hydrogenation of racemic α‐aryl‐β‐ethoxycarbonyl cyclopentanones via DKR for the synthesis of chiral cyclopentanols with three contiguous stereocenters was also demonstrated by Xie [76] et al . This reaction was successfully used for the synthesis of natural products such as (+)‐burmaniol A, (−)‐hamigeran B [77] and (−)‐hamigeran F [78] …”
Section: Asymmetric Hydrogenation Of C=o Bondsmentioning
confidence: 99%
“…We found that ( R )- 5e efficiently catalyzed the hydrogenation of functionalized racemic ketoesters, affording chiral cyclopentanols 37 in high yields with high enantioselectivities (up to 98% ee), cis , cis -selectivities up to >99:1, and TONs up to 10 000. This reaction was successfully used for the enantioselective synthesis of natural products such as hamigeran diterpenoids (−)-hamigeran B and (−)-hamigeran F and the phenylpropanoid (+)-burmaniol A (Figure a) …”
Section: Applications Of Iridium Catalysts With Tridentate Spiroap-ba...mentioning
confidence: 99%